Geopolitical tensions framing different industries in the European Arctic: aquaculture, forestry, mining, and tourism in question - Leena Suopajärvi; Juulia Tikkanen; Anna Guðrún Edvardsdóttir; Sigrid Engen; Esa Inkilä; Audun Iversen; Vigdis Nygaard; Rannveig Ólafsdóttir (Journal of Land Use Science)
Russia’s full-scale war on Ukraine in early 2022 has brought geopolitics, particularly classical geopolitics, back into the political and economic discussions and decision-making. Discursive, as well as real-world change, has been rapid, as the turn of the 21st century was the time of globalisation and neoliberal ideology – the free movement of people, products, and services. However, in this paper, we argue that classical geopolitics has defined the development of Northern industries even before the war began in 2022. Our interview data (n = 60) collected in the advent of the Russian invasion of Ukraine reveal that the themes of state power; ‘hard’ security meaning military armament; the economy as a field of national interests; and spill-over effects of geopolitical tensions between superpowers have framed economic fortunes in the European Arctic. It is concluded that the state actors’ interests in the European Arctic’s physical space and natural assets will be increasingly expanding.